A Perlocutionary Analysis of Fans’ Resonance in TikTok Comments on Justin Bieber’s Coachella Comeback Performance of Beauty and a Beat - Salwa Naila Humaira; Zaskia Fatimah; Cecilia Novalisa Situmorang; Salsa Aila; Ratu Aliqa Syahkirana Idham; Dian Marisha Putri (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2026)
Justin Bieber's performance of "Beauty and a Beat" at the 2026 Coachella Festival sparked extensive public discussion on TikTok, particularly over his altered vocal style and his use of a laptop during the live performance. This study investigates how audiences interpreted and responded to the performance by examining how perlocutionary acts are manifested in TikTok comments. Drawing upon J. L. Austin's speech act theory, the research employs a qualitative descriptive approach to analyze 100 TikTok comments related to the performance. The findings identify several categories of perlocutionary effects, with nostalgia emerging as the predominant audience response, indicating that viewers interpreted the performance through both emotional and experiential lenses. These results demonstrate that contemporary musical performances operate not merely as entertainment but also as communicative events that shape audience emotions, perceptions, and patterns of digital interaction. The study argues that applying perlocutionary speech act theory to social media discourse broadens the scope of digital pragmatics by providing deeper insights into audience engagement within online participatory cultures.